2013
DOI: 10.1155/2013/502697
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Antipsychotics on Prolactin Levels and Women’s Menstruation

Abstract: Introduction. Typical and atypical antipsychotic agent is currently used for treatment in the majority of patients with psychotic disorders. The aim of this review is to assess antipsychotic induced hyperprolactinaemia and the following menstrual dysfunction that affects fertility, quality of life, and therapeutic compliance of women. Method. For this purpose, Medline, PsychInfo, Cochrane library, and Scopus databases were accessed, with a focus on the publication dates between 1954 and 2012. Research of refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 69 publications
1
51
0
3
Order By: Relevance
“…However, there is no difference between women suffering from schizophrenia and healthy women in successfully reproducing over all ages. The lower rates may also be influenced by other variables not readily considered such as lower rates of sexual activity, difficulties maintaining stable romantic relationships [27], medication induced abnormalities in prolactin levels and menstruation (which can vary depending on which medication is taken) [28] and medication induced sexual dysfunction (30-80% in women) [29][30][31]. It has been shown that more than half of the women with psychosis in the sample for the McGarth group (1999) were mothers and had higher levels of fertility was associated with a later age at first diagnosis [32].…”
Section: Motherhood and Schizophreniamentioning
confidence: 99%
“…However, there is no difference between women suffering from schizophrenia and healthy women in successfully reproducing over all ages. The lower rates may also be influenced by other variables not readily considered such as lower rates of sexual activity, difficulties maintaining stable romantic relationships [27], medication induced abnormalities in prolactin levels and menstruation (which can vary depending on which medication is taken) [28] and medication induced sexual dysfunction (30-80% in women) [29][30][31]. It has been shown that more than half of the women with psychosis in the sample for the McGarth group (1999) were mothers and had higher levels of fertility was associated with a later age at first diagnosis [32].…”
Section: Motherhood and Schizophreniamentioning
confidence: 99%
“…1985). Prolaktin üzerine etkileri az olan olanzapin ve klozapin kullanımının tardiv diskineziye az oranda neden olduğu ve hatta tedavide kullanılabileceği belirtilmektedir (Bargiota 2013).…”
Section: Hareket Bozukluklarıunclassified
“…High Serum prolactin level can disturb the follicular maturation with corpus luteum function, and leads to inhibition of normal pulsatile secretion of gonadotrophins-releasing hormone in hypothalamus [8] . It also leads to deficient secretion of LH and FSH which leads to inadequate induction of proper ovarian response [9] .…”
Section: Introductionmentioning
confidence: 99%